Interstitial white matter neuron density in the dorsolateral prefrontal cortex and parahippocampal gyrus in schizophrenia. - Eastwood, S; Harrison, P (2005)
Alterations in the density or distribution of interstitial white matter neurons are taken as evidence in support of an early developmental component to schizophrenia. However, the existence and nature of interstitial white matter neuron changes in schizophrenia remain inconclusive. Recently, we reported that interstitial white matter neuron density is increased in the superficial white matter of the superior temporal gyrus in schizophrenia, but unchanged in deep white matter. This study extends our investigations to the dorsolateral prefrontal cortex and parahippocampal gyrus. Using the specific neuronal antibody NeuN, interstitial white matter neuron density was found to be increased in schizophrenia in the superficial white matter of the dorsolateral prefrontal cortex, with no significant changes elsewhere. As interstitial white matter neurons are presumed to be remnants of the embryonic cortical subplate, these findings provide additional evidence supportive of an early developmental abnormality in schizophrenia.